MANFAAT DAUN KUMIS KUCING SEBAGAI ANTI GLAUKOMA - Abdul Wahab; Siti Robiah Ajura (Jurnal Sains Riset, 2021)
Glaucoma is a condition in which the eye pressure (IOP) of a person is so high or abnormal that it causes damage to the optic nerve and results in partial or complete disruption of the field of view or blindness. Glaucoma will occur when the eye fluid inside the eyeball is disturbed. Judging from the various benefits of the Orthosiphon spicatus plant, it turns out that so far, ethanol extract of cat whiskers (Orthosiphon spicatus) can be used to reduce eye pressure (IOP) in glaucoma, one of which is a carbonic anhydrase inhibitor diuretic drug, acetazolamide. The purpose of this study was to determine the extra ethanol of Orthosiphon spicatus leaves and the comparison of Orthosiphon spicatus extra ethanol with anti-diuretic drugs to reduce intraocular pressure in male wistar strain rats with glaucoma. This type of research is a laboratory experimental study using a completely randomized design (CRD) with the Posttest Only Control Design method. Results The effect of extra ethanol leaves of Orthosiphon spicatus on intraocular pressure of mice with glaucoma was investigated. Glaucoma was obtained by inducing the animals with prednisolone acetate 1% eye drops every 5 minutes for 1 hour. 30 rats divided into 6 groups. Three groups of animals were given extracts at a dose of 12.36 and 108 mg / 200 g BW orally. In comparison, one normal control group, a negative control group and one group were treated with acetazolamide (4.5 mg / 200 g BW). The results showed that the extract reduced the intraocular pressure of mice with glaucoma especially at a dose of 36 mg / 200 g BW.Keywords: Orthosiphon spicatus, Glaucoma, Extra Ethanol, Wistar Strain Male Rats